Photocatalysis applications of some hybrid polymeric composites incorporating TiO(2) nanoparticles and their combinations with SiO(2)/Fe(2)O(3) - Chibac, Andreea Laura (Beilstein J Nanotechnol, 2017)
Polymer nanocomposites containing titanium oxide nanoparticles (TiO(2) NPs) combined with other inorganic components (Si–O–Si or/and γ-Fe(2)O(3)) were prepared by the dispersion of premade NPs (nanocrystalline TiO(2), TiO(2)/SiO(2), TiO(2)/Fe(2)O(3), TiO(2)/SiO(2)/Fe(2)O(3)) within a photopolymerizable urethane dimethacrylate (polytetrahydrofuran-urethane dimethacrylate, PTHF-UDMA). The physicochemical characterization of nanoparticles and hybrid polymeric composites with 10 wt % NPs (S1–S4) was realized through XRD, TEM and FTIR analyses. The mean size (10–30 nm) and the crystallinity of the NPs varied as a function of the inorganic constituent. The catalytic activity of these hybrid films was tested for the photodegradation of phenol, hydroquinone and dopamine in aqueous solution under UV or visible-light irradiation. The best results were obtained for the films with TiO(2)/Fe(2)O(3) or TiO(2)/SiO(2)/Fe(2)O(3) NPs. The degradation of the mentioned model pollutants varied between 71% and 100% (after 250 min of irradiation) depending on the composition of the hybrid film tested and the light applied (UV–visible light). Also, it was established that such hybrid films can be reused at least for five cycles, without losing too much of the photocatalytic efficiency (ca. 7%). These findings could have implications in the development of new nanocatalysts.